Focused Access to XML Documents - Fuhr, N. (Springer, 2017)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Workshop of the Initiative for the Evaluation of XML Retrieval, INEX 2007, held at Dagstuhl Castle, Germany, in December 2007.